First passenger train of the White Pass & Yukon Railroad on the summit of White Pass, Alaska, February 20, 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows crowd of men and women, some with cameras, standing in front of the train. Caption on image: ""White Pass and Yukon Route". First passenger train on the summit of White Pass. Feb 20 1899." Original image in Hegg Album 2, page 30.